2014
DOI: 10.7314/apjcp.2014.15.3.1391
|View full text |Cite
|
Sign up to set email alerts
|

MiR-130a Overcomes Gefitinib Resistance by Targeting Met in Non-Small Cell Lung Cancer Cell Lines

Abstract: Non-small cell lung cancer (NSCLC) is the most common type of lung cancer and the most common cause of lung cancer death. Currently, the epidermal growth factor receptor inhibitor gefitinib is used for its treatment; however, drug resistance is a major obstacle. Expression of Met has been associated with both primary and acquired resistance to gefitinib, but the mechanisms regulating its expression are not fully understood. Recently, miRNAs such as miR-130a have been shown to play a role in gefitinib resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 30 publications
1
37
0
Order By: Relevance
“…There were no significant differences between the two groups in terms of gender, age, international prognostic index (IPI) and stage. We investigated the pretreatment concentrations of serum miR-155, miR-200c, miR-29c, miR-130a, miR-145, miR-451, miR-125b and miR-21 expression levels, which have been reported in certain other tumor types to be associated with chemotherapy resistance (Table III) (9,14,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). We observed that only the expression of miR-130a and miR-125b was correlated significantly with the response to chemotherapy.…”
Section: Dysregulated Expression Profiles Of Eight Mirnas In Dlbclmentioning
confidence: 90%
See 1 more Smart Citation
“…There were no significant differences between the two groups in terms of gender, age, international prognostic index (IPI) and stage. We investigated the pretreatment concentrations of serum miR-155, miR-200c, miR-29c, miR-130a, miR-145, miR-451, miR-125b and miR-21 expression levels, which have been reported in certain other tumor types to be associated with chemotherapy resistance (Table III) (9,14,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). We observed that only the expression of miR-130a and miR-125b was correlated significantly with the response to chemotherapy.…”
Section: Dysregulated Expression Profiles Of Eight Mirnas In Dlbclmentioning
confidence: 90%
“…A number of previous studies have revealed that miRNAs are involved in the progress of drug resistance in certain types of cancer (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). These miRNAs might play a crucial role in drug resistance by targeting their specific genes.…”
mentioning
confidence: 99%
“…Adenocarcinoma cannot be treated adequately through simple operations. Therefore, chemotherapy remains the mainstay treatments for lung cancer (Wang et al, 2013;Zhou et al, 2014). Cisplatin, as the first line drug, is extensively applied for the clinical treatment of nonsmall-cell lung cancer (Fan and Jiang, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that miR-130a is associated with lung cancer [50], gastric cancer [51,52], ovarian cancer [53][54][55][56][57], cervical cancer [58,59], and prostate cancer [60]. Recently, deep sequencing technology was used to identify differentially expressed host miRNAs in chickens [28,34,35,61,62].…”
Section: Discussionmentioning
confidence: 99%